(untitled) (Eurasian Medical Research Periodical, 2024)
Malaria is a vector-borne infectious disease caused by Plasmodium parasites transmitted by infected female Anopheles mosquitoes. In tropical and subtropical countries, herbal medicine has gained popularity due to its therapeutic benefits, low cost, and bioavailability. This study evaluated the effect of co-administration of mangiferin and arthemeter-lumefantrine on serum lipids, cardiac enzymes, and heart histology in plasmodium berghei-infected Swiss albino mice. Forty-two (42) albino swiss mice were divided into seven groups, with four groups infected with the blood of highly parasitized P. berghei-infected mice, while three were control groups. Arthemeter Lumefantrine (AL) was administered as the standard drug, and Mangiferin was used for treating the parasite. Group 1 was the normal control and received normal feed and water ad libitum. Group 2 was infected with P. berghei; Groups 3 and 4 were treated with 8 mg/kg body weight of arthemeter-lumefatrine and 410.79 mg/kg of mangiferin, respectively. Groups 5 and 6 were infected with P. berghei and treated with 8 mg/kg body weight of ArthemeterLumefantrine and 410.79 mg/kg of Mangiferin, respectively. Group 7 was infected with P. berghei and treated with Arthemeter-Lumefantrine and Mangiferin at doses of 8 mg/kg and 410.79 mg/kg body weight, respectively. The study discovered that giving mangiferin and AL together had a big effect on the lipid profile and heart function of mice that had been paralyzed, which suggests that the heart might be protected. The study recommends investigating possible drug interactions between mangiferin and other commonly used drugs in Africa to ensure that combining treatments doesn’t negatively impact or decrease their effectiveness